Preparation method of porous vermicular CoO-PS composite material, composite material and application

Porous worm-like CoO-PS composite material was prepared by dissolving, miscible, euthanization, and heat treatment of cobalt salt acetic acid solution and polystyrene halogenated hydrocarbon solution, which solved the problem of complex process and low economic benefits in the recycling and utilization of waste polystyrene, and achieved efficient and low-cost composite material preparation.

CN119500084APending Publication Date: 2025-02-25HEBEI UNIV OF ENG
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411731872.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

In the prior art, the recycling and utilization of waste polystyrene has problems such as complex process steps, expensive reaction reagents, and low economic benefits.

Method used

Porous worm-like CoO-PS composite material was prepared by adding acetic acid solution of cobalt salt to a halogenated hydrocarbon solution of polystyrene and following simple process steps such as dissolution-misolution-eutexamination-heat treatment.

Benefits of technology

The combination of polystyrene and cobalt salt at the micro-nano level is achieved, and the obtained composite material has excellent carbonization and activation properties. The overall process is simple, easy to operate, and low energy consumption, overcoming the shortcomings in the preparation method present in the prior art.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119500084A_ABST
    Figure CN119500084A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method of a porous vermicular CoO-PS composite material, the vermicular CoO-PS composite material prepared by the method and application of the vermicular CoO-PS composite material. The method comprises the following steps: adding an acetic acid solution of a metal compound into a halogenated hydrocarbon solution of polystyrene, heating to 50-80 DEG C, uniformly stirring to obtain a mixed liquid, and keeping the temperature for a period of time; and cooling the mixed liquid to normal temperature, and carbonizing the precipitate obtained by filtering at high temperature to obtain the porous wormlike CoO-PS composite material. The method is simple in process step, mild in reaction condition and low in material consumption and energy consumption, and the prepared porous wormlike CoO-PS composite material is large in specific surface area and high in adsorption capacity and can be used as an adsorption material or a photocatalytic material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of recycling waste polystyrene, and in particular to a method for preparing a porous worm-like CoO-PS composite material based on waste polystyrene, and the porous worm-like CoO-PS composite material prepared by the method and applications thereof. Background Art

[0002] Polystyrene (PS) is a general-purpose thermoplastic plastic that is widely used in various fields due to its excellent product performance. At present, most polystyrene materials are disposable products, which are discarded at will after use, thus generating a large amount of waste. These solid wastes are light in weight, large in volume, and chemically stable. They are difficult to degrade in the natural environment for a long time, causing environmental pollution. Therefore, the recycling and utilization of waste polystyrene is of great significance.

[0003] At present, the main technologies for recycling and utilizing waste polystyrene (PS) include the following two approaches: One is recycling. For example, Chinese patent CN 101307150 B invented a low-cost method for recycling waste polystyrene, which involves hot pressing the waste polystyrene at low temperature, dissolving it in a good solvent of polystyrene, filtering it once to remove insoluble impurities, decolorizing it, adding a precipitant to precipitate it, filtering it twice, and other processes to recycle the waste polystyrene into polystyrene pellets. The recycled pellets can continue to produce polystyrene downstream products. Chinese patent CN 101701073 B involves a method for functionalizing and reshaping waste polystyrene, which involves pre-treating the polystyrene foam, adding it to a water-insoluble organic solvent to dissolve it into a polystyrene swollen body, adding it to water containing a surfactant, and obtaining finished polystyrene particles after continuous stirring, heating and distillation, and solid-liquid separation, and then soaking it in a foaming agent to obtain expandable polystyrene particles (EPS). For another example, Chinese patent CN 115572410 A provides a method for recycling and reusing waste polystyrene. The method first performs swelling and dissolution on the waste polystyrene in water at 140 to 300° C. Since the waste polystyrene will swell and depolymerize in water at 140 to 300° C., at the same time, the waste polystyrene can achieve self-chain segment stretching and depolymerization at 140 to 300° C., under the action of the above-mentioned dual depolymerization mechanism, the polystyrene is reshaped.

[0004] The second is to prepare chemicals. For example, Chinese patent CN 101423738 B invented a method for preparing non-toxic adhesives using waste polystyrene foam and waste plastics, and the process steps are as follows: (1) shearing and crushing waste polystyrene foam into powder particles with a particle size of 16 to 32 mesh, and then washing and drying; (2) dissolving with a mixed solvent of ethyl acetate and d-limonene; (3) adding plasticizer dibutyl phthalate and stirring at 76 to 78°C for 60 minutes; (4) adding acrylic acid and maleic anhydride mixed modifiers, heating and stirring; (5) cooling to 50 to 55°C, then adding OP-10 emulsifier and sodium dodecylbenzene sulfonate, heating and stirring to mix evenly; (6) adjusting the pH value of the emulsion, adding a small amount of sodium hydroxide solid powder, and adjusting its pH value to 5 to 6, so as to obtain a milky white viscous emulsion adhesive. The disadvantages of this invention method are that the process steps are complicated and some reagents are expensive. Another example is China's CN 101691425 B, which invented a method for preparing an adsorbent resin material using waste polystyrene foam plastics as raw materials. The invention prepares waste polystyrene (PS) foam plastics into small spherical adsorbent resin materials by suspension copolymerization. However, the preparation process requires dissolving a certain amount of waste polystyrene (PS) with styrene monomer (St), and requires the use of divinylbenzene (cross-linking agent), benzoyl peroxide (initiator), n-heptane (porogen), polyvinyl alcohol (stabilizer) and other reagents, which reduces the economic efficiency of waste utilization. Another example is China's patent CN 113071024 B, which invented a method for recycling waste plastics to prepare foam products, including the steps of waste plastic selection and pre-drying treatment, primary impurity removal, secondary water washing, cold pressing, crushing, volume reduction and defoaming, rinsing, melt extrusion, granulation water cooling, re-foaming, maturation and molding. The invention can realize the recycling and reuse of waste expandable polystyrene, but the disadvantages are that the process is long and the organic content of the generated wastewater is high.

[0005] Chinese patent CN 116284880 A discloses a method for preparing halogen-free flame-retardant polystyrene beads and expandable polystyrene beads using waste polystyrene. The invention uses a non-water-soluble composite halogen-free flame retardant and waste polystyrene as raw materials, adopts a dissolution-distillation-suspension method to achieve effective compounding of the flame retardant and polystyrene, prepares halogen-free flame-retardant polystyrene beads, and then adds a foaming agent to prepare halogen-free flame-retardant expandable polystyrene beads.

[0006] In the prior art, the utilization of waste polystyrene has problems of complex process steps, expensive reaction reagents, and low economic benefits to varying degrees. Therefore, developing new utilization methods for waste polystyrene has always been the goal pursued by scientific and technological workers. Summary of the invention

[0007] The purpose of the present invention is to develop a new way to utilize waste polystyrene and provide a method for preparing a worm-like CoO-PS composite material from waste polystyrene.

[0008] The method of the invention comprises the following steps: adding an acetic acid solution of a cobalt salt with a mass concentration of 0.01-0.1 g / mL to a halogenated hydrocarbon solution of polystyrene with a mass concentration of 0.01-0.15 g / mL according to a volume ratio of 1 / 1-1 / 3, then heating to 50-80°C and stirring evenly to obtain a mixed liquid, and keeping the temperature constant for 2 h-12 h; then cooling the mixed liquid to room temperature, filtering the precipitated precipitate, collecting the precipitate, and subjecting the precipitate to high-temperature heat treatment to obtain a porous worm-like CoO-PS composite material.

[0009] Preferably, the cobalt salt is cobalt acetate or cobalt nitrate.

[0010] Preferably, the halogenated hydrocarbon solvent comprises any one of dichloromethane and chloroform.

[0011] Preferably, in the halogenated hydrocarbon solution of polystyrene, the particle size of polystyrene is 1 nm-100 nm.

[0012] Preferably, the temperature of the high temperature heat treatment is 500-850° C., and the carbonization time is 1 h-6 h.

[0013] The present invention also relates to a worm-like metal-doped carbon material prepared by the above-mentioned preparation method. The metal-doped carbon material has a uniform worm-like and porous structure and can be applied to the fields of adsorption materials, photocatalytic materials, etc.

[0014] Compared with the prior art, the present invention has the following advantages and beneficial effects: (1) The present invention provides a method for preparing a worm-like CoO-PS composite material. The method comprises the following steps: dissolving polystyrene (PS) with a conventional low-boiling point solvent by optimizing a solvent, and then mixing the solvent with a metal compound solution. The worm-like CoO-PS composite material is obtained through simple process steps such as dissolution-miscibility-eutectoid-heat treatment. The reagents used in the overall process are green, cheap and easy to obtain. The obtained CoO-PS composite material is worm-like and has a uniform porous structure. The composite material can be applied to adsorption materials, photocatalytic materials and other fields, and provides a new way to efficiently and effectively utilize waste polystyrene.

[0015] (2) After a large number of tests and optimization, the method of the present invention has found that by adding an acetic acid solution of a cobalt salt to a halogenated hydrocarbon solution of polystyrene, according to a certain material ratio, the polystyrene and the cobalt salt can be combined at the micro-nano level through a dissolution-miscibility-eutectoid-heat treatment process, thereby increasing the contact area between the cobalt salt and the polystyrene under mild conditions. The obtained cobalt salt-polystyrene intermediate material has excellent carbonization and activation properties. The overall method is simple in process, easy to operate and control, and has low material and energy consumption. It also overcomes the technical problems existing in the existing preparation methods of metal compound-modified polystyrene materials, such as the difficulty in crushing the carbon source material and the difficulty in uniformly mixing it with the activator, resulting in a small effective contact area between the two, a large amount of activator, uneven reaction, and low product yield.

[0016] (3) In the preferred technical solution of the present invention, the solvent used has a low boiling point and can be recycled and reused, which further greatly reduces the cost of recycling and processing waste polymer materials and increases the value of the recycled products. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 The cobalt acetate-polystyrene intermediate samples prepared in Examples 1-5 and the microscope magnified optical photographs of the samples.

[0018] Figure 2 This is a Fourier infrared spectrum of the cobalt acetate-polystyrene intermediate prepared in Example 1-5 of the present invention.

[0019] Figure 3 This is a scanning electron microscope image of the CoO-PS composite material prepared in an embodiment of the present invention. DETAILED DESCRIPTION

[0020] The following examples are given to specifically describe the preferred embodiments of the present invention. It is necessary to point out that the following examples cannot be understood as limiting the scope of protection of the present invention. Those skilled in the art can make some non-essential improvements and adjustments to the present invention based on the content of the present invention. Any simple modifications and equivalent changes made to the following examples based on the technical concept of the present invention fall within the scope of protection of the present invention. Example 1

[0021] The waste polystyrene was crushed into particles smaller than 0.5 cm × 0.5 cm, and then 1 g of the waste polystyrene particle sample was dissolved in 30 mL of chloroform solvent to obtain solution A; Dissolve 1 g of cobalt acetate in 15 mL of acetic acid solvent to obtain solution B; Solution A and solution B are mixed in a volume ratio of 1:1, placed in a closed container, and then placed in an oven and heated to 60° C., and kept at a constant temperature for 24 hours; the closed container is taken out, cooled naturally to room temperature, and the mixed solution in the container is filtered to obtain a polystyrene-cobalt acetate composite sample; The obtained composite was dried at 105 to 110° C. for 10 to 20 min, and then the dried product was placed in a muffle furnace and carbonized at 500° C. for 3 h to obtain a porous worm-like cobalt-doped carbon material.

[0022] Figures 1 to 3 They are respectively the cobalt acetate-polystyrene intermediate sample prepared in Example 1 and a microscope magnified optical photograph of the sample, a Fourier transform infrared spectrum of the cobalt acetate-polystyrene intermediate and a scanning electron microscope image of the finally obtained CoO-PS composite material.

[0023] Depend on Figure 1 It can be seen that the cobalt acetate-polystyrene intermediate obtained by the method of the present invention is in the form of a gray powder. Microscopic observation shows that the sample has uniform color and no obvious phase separation phenomenon, indicating that cobalt acetate and polystyrene are uniformly mixed.

[0024] Figure 2 It shows that in the infrared spectra of cobalt acetate-polystyrene intermediates prepared under different conditions, 3050cm -1 The left and right are the characteristic peaks of the CH bond on the benzene ring, 2930 cm -1 The absorption peaks on the left and right are the stretching vibrations of saturated CH bonds, 1561 cm -1 、1417cm -1 The absorption peak at 1034 cm is the stretching vibration peak of the C=C double bond on the benzene ring. -1 The absorption peak at is the vibration peak of the CO bond, indicating that the cobalt acetate-polystyrene intermediate obtained by dissolution-miscibility-eutectoid treatment has achieved chemical modification of polystyrene by cobalt acetate to some extent.

[0025] Figure 3 This is a scanning electron microscope image of the cobalt acetate-polystyrene composite material obtained after high-temperature heat treatment of the cobalt acetate-polystyrene intermediate prepared in Example. It can be clearly seen from the image that the composite material has a uniform product morphology at the microscopic scale and presents a worm-like structure. Example 2

[0026] The waste polystyrene was crushed into particles smaller than 0.5 cm×0.5 cm, and then 2 g of the waste polystyrene particle sample was dissolved in 30 mL of dichloromethane solvent to obtain solution C; Dissolve 1 g of cobalt acetate in 10 mL of acetic acid solvent to obtain solution D; Solution C and solution D were mixed in a volume ratio of 1:2, placed in a closed container, and then placed in an oven and heated to 50°C for 36 h, then taken out and allowed to stand naturally to cool to room temperature; filtering the mixed solution in the container to obtain a polystyrene-cobalt acetate complex; The obtained composite was dried at 105 to 110° C. for 10 to 20 min, and then the dried product was placed in a muffle furnace and carbonized at 800° C. for 1 h to obtain a porous worm-like cobalt acetate-polystyrene composite material.

[0027] The sample of the cobalt acetate-polystyrene intermediate obtained in this example, the microscope magnified optical photograph of the sample, the Fourier transform infrared spectrum of the cobalt acetate-polystyrene intermediate and the scanning electron microscope image of the finally obtained CoO-PS composite material are consistent with those in Example 1 and are not listed again here. Example 3

[0028] The waste polystyrene was crushed into particles smaller than 0.5 cm×0.5 cm, and then 5 g of the waste polystyrene particle sample was dissolved in 30 mL of dichloromethane solvent to obtain solution E; Dissolve 2 g of cobalt acetate in 30 mL of acetic acid solvent to obtain solution F; Solution E and solution F were mixed in a volume ratio of 1:1 and placed in a closed container. The mixture was then placed in an oven and heated to 80°C for 12 h. The mixture was then taken out and allowed to stand naturally to cool to room temperature. filtering the mixed solution in the container to obtain a polystyrene-cobalt acetate complex; The obtained composite was dried at 105 to 110° C. for 10 to 20 min, and then the dried product was placed in a muffle furnace and carbonized at 700° C. for 6 h to obtain a porous worm-like cobalt acetate-polystyrene composite material.

[0029] The sample of the cobalt acetate-polystyrene intermediate obtained in this example, the microscope magnified optical photograph of the sample, the Fourier transform infrared spectrum of the cobalt acetate-polystyrene intermediate and the scanning electron microscope image of the finally obtained CoO-PS composite material are consistent with those in Example 1 and are not listed again here. Example 4

[0030] The waste polystyrene was crushed into particles smaller than 0.5 cm × 0.5 cm, and then 1.5 g of the waste polystyrene particle sample was dissolved in 30 mL of dichloromethane solvent to obtain solution G; Dissolve 2 g of cobalt acetate in 20 mL of acetic acid solvent to obtain solution H; Solution G and solution H were mixed in a volume ratio of 1:2 and placed in a closed container. The mixture was then placed in an oven and heated to 50°C for 48 h. The mixture was then taken out and allowed to stand naturally to cool to room temperature. filtering the mixed solution in the container to obtain a polystyrene-cobalt acetate complex; The obtained composite was dried at 105 to 110° C. for 10 to 20 min, and then the dried product was placed in a muffle furnace and carbonized at 800° C. for 6 h to obtain a porous worm-like cobalt acetate-polystyrene composite material.

[0031] The sample of the cobalt acetate-polystyrene intermediate obtained in this example, the microscope magnified optical photograph of the sample, the Fourier transform infrared spectrum of the cobalt acetate-polystyrene intermediate and the scanning electron microscope image of the finally obtained CoO-PS composite material are consistent with those in Example 1 and are not listed again here. Example 5

[0032] The waste polystyrene was crushed into particles smaller than 0.5 cm×0.5 cm, and then 3 g of the waste polystyrene particle sample was dissolved in 30 mL of dichloromethane solvent to obtain solution I; Dissolve 1 g of cobalt nitrate in 20 mL of acetic acid solvent to obtain solution J; Solution I and solution J were mixed in a volume ratio of 1:3 and placed in a closed container. The mixture was placed in an oven and heated to 60°C for 32 h. The mixture was then taken out and allowed to cool naturally to room temperature. filtering the mixed solution in the container to obtain a cobalt acetate-polystyrene complex; The obtained composite was dried at 105 to 110° C. for 10 to 20 min, and then the dried product was placed in a muffle furnace and carbonized at 850° C. for 6 h to obtain a porous worm-like cobalt acetate-polystyrene composite material.

[0033] The sample of the cobalt acetate-polystyrene intermediate obtained in this example, the microscope magnified optical photograph of the sample, the Fourier transform infrared spectrum of the cobalt acetate-polystyrene intermediate and the scanning electron microscope image of the finally obtained CoO-PS composite material are consistent with those in Example 1 and are not listed again here. Example 6

[0034] The waste polystyrene was crushed into particles smaller than 0.5 cm×0.5 cm, and then 1.5 g of the waste polystyrene particle sample was dissolved in 30 mL of dichloromethane solvent to obtain solution K; Dissolve 1 g of cobalt chloride in 20 mL of acetic acid to obtain solution L; Solution I and solution J were mixed in a volume ratio of 1:3 and placed in a closed container. The mixture was placed in an oven and heated to 60°C. The mixture was kept at this temperature for 24 h and then taken out and allowed to cool naturally to room temperature. filtering the mixed solution in the container to obtain a cobalt acetate-polystyrene complex; The obtained composite was dried at 105 to 110° C. for 10 to 20 min, and then the dried product was placed in a muffle furnace and carbonized at 600° C. for 4 h to obtain a porous worm-like cobalt acetate-polystyrene composite material.

[0035] The sample of the cobalt acetate-polystyrene intermediate obtained in this example, the microscope magnified optical photograph of the sample, the Fourier transform infrared spectrum of the cobalt acetate-polystyrene intermediate and the scanning electron microscope image of the finally obtained CoO-PS composite material are consistent with those in Example 1 and are not listed again here.

[0036] The above are only some of the preferred specific implementation methods of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical solutions and concepts of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A method for preparing a porous worm-like CoO-PS composite material, characterized in that: include: An acetic acid solution of a cobalt salt with a mass concentration of 0.01-0.1 g / mL is added to a halogenated hydrocarbon solution of polystyrene with a mass concentration of 0.01-0.15 g / mL in a volume ratio of 1 / 1-1 / 3, and then heated to 50-80°C and stirred evenly to obtain a mixed liquid, which is kept at a constant temperature for 2 h-12 h; then the mixed liquid is cooled to room temperature, the precipitated precipitate is filtered, the precipitate is collected, and a porous worm-like CoO-PS composite material is obtained by high-temperature heat treatment.

2. The method for preparing the porous worm-like CoO-PS composite material according to claim 1, characterized in that: The cobalt salt is any one of cobalt acetate or cobalt nitrate.

3. The method for preparing the porous worm-like CoO-PS composite material according to claim 1, characterized in that: The halogenated hydrocarbon solvent includes any one of dichloromethane and chloroform.

4. The method for preparing the porous worm-like CoO-PS composite material according to claim 1, characterized in that: In the polystyrene halogenated hydrocarbon solution, the particle size of the polystyrene is 1 nm-100 nm.

5. The method for preparing the porous worm-like CoO-PS composite material according to claim 1, characterized in that: The high temperature carbonization temperature is 500-850° C., and the carbonization time is 1h-6h.

6. The method for preparing the porous worm-like CoO-PS composite material according to any one of claims 1 to 5, characterized in that: The polystyrene is waste polystyrene.

7. The method for preparing the porous worm-like CoO-PS composite material according to any one of claims 1 to 5, characterized in that: The polystyrene is crushed into particles smaller than 0.5 cm×0.5 cm before use.

8. A porous worm-like CoO-PS composite material, characterized in that: The porous worm-like CoO-PS composite material is prepared by the preparation method of any one of claims 1 to 6.

Citation Information

Patent Citations

  • Novel method for recovering waste and old polystyrol

    CN101307150B

  • Method for preparing non-toxic adhesive by using waste and old polystyrol

    CN101423738B

  • Method for preparing adsorptive resin materials by utilizing waste polystyrene

    CN101691425B

  • Method for functionally remolding waste polystyrene

    CN101701073B

  • A method for recycling waste plastics to prepare foam products

    CN113071024B